P. B. Vachha's famous judges, lawyers and cases of Bombay: a judicial history of Bombay during the British period - Vachha, P.B. (New Delhi, 2012)
This book emphasized on the Vachha's history of the Bombay High Court. Author written this history mainly with an eye to the picturesque so as to make it interesting to the general readers, beside those directly connected with law and law courts. It emphasized on origin and background of law courts in Bombay, first British court of law in Bombay, East India Company's Adawlats, ICS Judges etc.
Keywords: Courts-India-Mumbai